2021
DOI: 10.1038/s41598-021-94361-8
|View full text |Cite
|
Sign up to set email alerts
|

Management of biliary diseases after the failure of initial needle knife precut sphincterotomy for biliary cannulation

Abstract: Endoscopic retrograde cholangiopancreatography is not always successful even with needle knife precut sphincterotomy (NKPS). How to manage these patients with initial NKPS failure has not been well studied. We report the outcomes of patients who received endoscopic and non-endoscopic rescue treatment after the initial NKPS failure. During the 15 years from 2004 to 2018, 87 patients with initial NKPS failure received interval endoscopic treatment (IET group, n = 43), percutaneous transhepatic biliary drainage (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…NKP was performed immediately after the failure of the conventional cannulation methods during the same endoscopic session. The NKP method was the same as that described in our previous study 24 , as shown in Fig. 1 .…”
Section: Methodsmentioning
confidence: 99%
“…NKP was performed immediately after the failure of the conventional cannulation methods during the same endoscopic session. The NKP method was the same as that described in our previous study 24 , as shown in Fig. 1 .…”
Section: Methodsmentioning
confidence: 99%
“…In a literature search in early 2022, we were only able to find 7 studies (371 patients in total) reporting interval ERCP[ 9 , 12 - 17 ]. All of these studies were retrospective.…”
Section: Interval Ercpmentioning
confidence: 99%
“…There were no review/meta-analysis articles on this topic. However, when SBC cannot be achieved by advanced cannulation techniques, such as NKP or NKF, these studies have shown that interval ERCP is a viable treatment option (Table 1 )[ 9 , 12 - 17 ]. The overall success rate of interval ERCP was 76.3% (68%-79% between studies).…”
Section: Interval Ercpmentioning
confidence: 99%
See 2 more Smart Citations